Analysis of Phenological Observations of Soybean 6310 and 7213 Collection Samples (Texas Journal of Agriculture and Biological Sciences, 2023)
In this article, ew describe the results of the phenological observation and analisis of soybean germination, flovering and pot phases for 6310 and 7213 samples